ANALYSIS OF TEMPE PRODUCTION MICRO BUSINESS STRATEGY IN INCREASING INCOME IN THE COVID-19 PANDEMIC USING SOAR ANALYSIS - Imsar Imsar; Juliana Nasution; Maulana Abdul Fattah (Jurnal Ekonomi, 2022)
The Covid-19 pandemic has caused a significant drop in income for business actors. This type of research is field research (field research), and the location of the study is on the micro business of barakah tempe production. The purpose of this study was to determine internal and external factors in the SOAR analysis (Strengths, Opportunities, Aspirations, and Results) on the strategies implemented by the Barokah tempe production micro business and to find out alternative plans for the Barokah tempe production micro business in increasing income during the Covid-19 pandemic. 19. Methods of data collection using interviews, observation and documentation. The data analysis technique is a qualitative descriptive analysis using SOAR analysis. The researcher uses the SOAR analysis technique because, in previous studies, no one has used SOAR analysis in solving problems regarding alternative strategy variables for micro-production businesses. The results showed that the IFAS score was 3.38 and the EFAS score was 3.31, so in the IE matrix, it can be seen that the internal and external factors in the SOAR analysis of the strategy implemented by the Barokah tempe production micro business are at the grow and build stage. The alternative method for the Barokah tempeh production micro business is to utilize good taste in attracting customers, Utilise the owner's knowledge to produce tempeh with a consistent taste, Focus on product variations to attract new customers, and make the Barokah tempe production micro business always able to compete in terms of product form; take advantage of strategic locations to better explore other consumers.